A molecular phylogeny of historical and contemporary specimens of an under‐studied micro‐invertebrate group. Issue 1 (9th December 2020) - Orr, Russell J. S.; Sannum, Maja M.; Boessenkool, Sanne; Di Martino, Emanuela; Gordon, Dennis P.; Mello, Hannah L.; Obst, Matthias; Ramsfjell, Mali H.; Smith, Abigail M.; Liow, Lee Hsiang
Abstract: Resolution of relationships at lower taxonomic levels is crucial for answering many evolutionary questions, and as such, sufficiently varied species representation is vital. This latter goal is not always achievable with relatively fresh samples. To alleviate the difficulties in procuring rarer taxa, we have seen increasing utilization of historical specimens in building molecular phylogenies using high throughput sequencing. This effort, however, has mainly focused on large‐bodied or well‐studied groups, with small‐bodied and under‐studied taxa under‐prioritized. Here, we utilize both historical and contemporary specimens, to increase the resolution of phylogenetic relationships among a group of under‐studied and small‐bodied metazoans, namely, cheilostome bryozoans. In this study, we pioneer the sequencing of air‐dried cheilostomes, utilizing a recently developed library preparation method for low DNA input. We evaluate a de novo mitogenome assembly and two iterative methods, using the sequenced target specimen as a reference for mapping, for our sequences. In doing so, we present mitochondrial and ribosomal RNA sequences of 43 cheilostomes representing 37 species, including 14 from historical samples ranging from 50 to 149 years old. The inferred phylogenetic relationships of these samples, analyzed together with publicly available sequence data, are shown in a statistically well‐supported 65 taxa and 17 genes cheilostome tree, which is also the most broadly sampled and largest to date. The robust phylogenetic placement of historical samples whose contemporary conspecifics and/or congenerics have been sequenced verifies the appropriateness of our workflow and gives confidence in the phylogenetic placement of those historical samples for which there are no close relatives sequenced. The success of our workflow is highlighted by the circularization of a total of 27 mitogenomes, seven from historical cheilostome samples. Our study highlights the potential of utilizing DNA from micro‐invertebrate specimens stored in natural history collections for resolving phylogenetic relationships among species. Abstract : Here, we present a workflow that utilizes historical and contemporary specimens, to increase the resolution of phylogenetic relationships among understudied and small‐bodied metazoans, namely, cheilostome bryozoans. In doing so, we present mitochondrial and ribosomal RNA sequences of 43 cheilostomes representing 37 species, including 14 from historical samples ranging from 50 to 149 years old, circularizing a total of 27 mitogenomes, seven from historical cheilostome samples. Our study highlights the potential of utilizing DNA from micro‐invertebrate specimens stored in natural history collections for resolving phylogenetic relationships between species.